1989
DOI: 10.1002/pola.1989.080271304
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of (o‐methylphenyl)acetylene and polymer characterization

Abstract: (o‐Methylphenyl)acetylene polymerized with high yields in the presence of W and Mo catalysts. W catalysts were more active than the corresponding Mo catalysts. The weight‐average molecular weight of the polymer formed with W(CO)6–CCl4–hv reached 8 × 105, being higher than the maximum value (ca. 2 × 105) for poly(phenylacetylene). The polymer had the structure \documentclass{article}\pagestyle{empty}\begin{document}$\rlap{--} [{\rm CH} \hbox{=\hskip-1pt=} {\rm C}(o - {\rm CH}_3 {\rm C}_6 {\rm H}_4 )\rlap{--} ]_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…All the three W catalysts in the table polymerize this monomer in over 65% yields. The polymers obtained with WCl6-Ph4Sn and W(CO) 6 -hv possess Mw's around 2 x 10 5 . MoCl 5 and its mixture with Ph4Sn also form poly(o-iso-PrPA)s quantitat- In order to gain knowledge on the relative reactivity of ortho-substituted monomers, their copolymerizations with phenylacetylene were carried out in toluene at 30°C;…”
Section: Polymerization Of ( O-iso-propylphenyl)acetylenementioning
confidence: 98%
See 3 more Smart Citations
“…All the three W catalysts in the table polymerize this monomer in over 65% yields. The polymers obtained with WCl6-Ph4Sn and W(CO) 6 -hv possess Mw's around 2 x 10 5 . MoCl 5 and its mixture with Ph4Sn also form poly(o-iso-PrPA)s quantitat- In order to gain knowledge on the relative reactivity of ortho-substituted monomers, their copolymerizations with phenylacetylene were carried out in toluene at 30°C;…”
Section: Polymerization Of ( O-iso-propylphenyl)acetylenementioning
confidence: 98%
“…1 • 5 W(C0) 6 -hv catalyst) and good thermal stability. 6 It has recently been found that phenylacetylenes with even bulkier ortho groups (e.g., CF 3 7 and Me 3 Si 8 • 9 ) yield polymers with very high molecular weight (Mw 1 x 10 6 and above).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By processing composition data (Tab.2) according to the KT equation (6) and NLLSprocedure, the FA-and r~~-v a l u e s were calculated. The results obtained are compiled in Tab.3.…”
Section: Determination Of Reactivity Ratiosmentioning
confidence: 99%